STRATEGY FOR DEVELOPING VILLAGE OWNED BUSINESS ENTITIES (BUMDES) IN IMPROVING THE VILLAGE ECONOMY IN KERTAJAYA VILLAGE, PADALARANG DISTRICT, WEST BANDUNG - Toto Kushartono; Bayu Septiansyah; Siti Munawaroh (Jurnal Caraka Prabu, 2023)
Village-Owned Enterprises are economic institutions at the village level to manage village potential and prosper the village community which is managed by the village government together with the community. This study aims to determine the Strategy for the Development of Village Owned Enterprises (BUMDES) in Improving the Village Economy in Kertajaya Village, Padalarang District, West Bandung Regency. The various potentials of the village as an attraction for development resources should be utilized properly by stakeholders (interested) in an effort to promote equitable development. The research method used is a descriptive method with an inductive approach. Data collection techniques used are interviews, observation, and documentation. The results of the study indicate that the strategy for developing BUMDes in improving the village economy in Kertajaya Village is trying to be carried out as much as possible even though it has not been able to significantly improve the community's economy, this is due to the Covid-19 pandemic. However, the village government tries to carry out several strategies such as providing money from the beginning to BUMDes, and there are several business items that are constant so that BUMDes can still run such as selling ATK needs and so on, providing capital to MSMEs, maximizing the existing budget to develop the BUMDes economy. Kertajaya and Bumdes villages can run even with the Covid-19 pandemic, absorption of community resources by boosting PAD, community empowerment in developing the village economy, making E-warung innovations to control the village economy, food security programs that are 20% of village funds by providing training , providing tools such as livestock seeds, agricultural seeds, with fertilizers, the Budikdamber program (Fish Cultivation in a Bucket) where the village government provides plant seeds assistance.